Continuous improvement practice in local government : insights from Australia and New Zealand - Pepper, Matthew; Price, Oriana; Elias, Arun (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book looks at continuous improvement (CI) methodologies and the application of such in local government in Australia and New Zealand. Through case studies, the book translates theoretical concepts into real life applications and thus, highlights the theory-practice nexus. The cases provides theoretically informed narratives of how approaches have been applied by practitioners in the implementation of CI in their organisations. It also demonstrates the benefits of academic-industry collaboration in the CI discipline. This book will be a useful reference to scholars and researchers working on process improvements, service processes, public management, public administration and as well as policy makers from the public sector"--
OCLC-licensed vendor bibliographic record.
Keywords: Local government -- Australia; Local government -- New Zealand; Continuous improvement process -- Australia; Continuous improvement process -- New Zealand; BUSINESS & ECONOMICS / Total Quality Management; BUSINESS & ECONOMICS / Quality Control